A wide tuning range Gm-C complex filter with master-slave automatic frequency tuning based switched-capacitor. (November 2018) - Wu, Jianhui; Xie, Zushuai; Yu, Tianji; Chen, Chao
Abstract: A wide tunable Gm-C complex filter with programmable operational transconductance amplifier (OTA) is presented in this paper. With automatic tuning of the master-slave stage, the filter's time constant C ∕ G m is set to a fixed value. Programmable OTA prevails wider tunable range. To achieve high linearity, an optimized differential OTA structure based on second-generation current conveyors (CCIIs) is employed for achieving wider tuning range in the complex filter. And the linearity of the filter suffers less from the master frequency tuning circuit because of no modification in the inner V-I conversion core during the tuning course. Benefited from the virtual ground created by the amplifier in switched-capacitor circuit, higher tuning accuracy is obtained. The prototype of the filter was fabricated in SMIC 0.18-μm CMOS process. Measurement results show that the tunable center frequency ranges from 147 kHz to 1.95 MHz and the tunable bandwidth ranges from 94 kHz to 1.96 MHz. Meanwhile, the filter achieves an in-band IIP3 above 18.2 dBm.